Population Trends in Herring Gulls (Larus argentatus), Great Black-backed Gulls (Larus marinus) and Lesser Black-backed Gulls (Larus fuscus fuscus) in Finland - Hario, Martti; Rintala, Jukka (Waterbird Soc., 2016)
After an increase from the 1930s through the mid-1990s, the populations of the Herring Gull (Larus argentatus), the Lesser Black-backed Gull (L. fuscus fuscus), and the Great Black-backed Gull (L. marinus) in Finland are currently declining at rates of 0.5%, 2.7%, and 1.5% per annum, respectively. Although now declining in numbers, the Herring Gull is still the dominant gull species on Finnish coasts. The nominate Lesser Black-backed Gull, formerly the most abundant large gull in the Baltic Sea, is now considered endangered over its entire range. The Great Black-backed Gull has largely followed the trajectories of the other two species, but in much lower numbers. The decline of the Lesser Black-backed Gull may have been caused by severe reproductive failures due to pollutants and predation, while the factors behind the declines of the other two species are largely unknown.
Keywords: coastal gulls; great black-backer gull; Herring gull; Larus argentatus; Larus fuscus fuscus; Larus marinus; lesser black-backed gull; population trends; Finland; f-fuscus